Parameter optimization of metal injection moulding: a review - Prathabrao, M; Ibrahim, M H I; M Amin, Sri Yulis; Othman, M H (Faculty of Mechanical Engineering, Universiti Teknologi MARA (UiTM), 2018)
Metal injection moulding (MIM) is a newly developed technology to form metals and alloys into desired shape. MIM is a combination of conventional plastic injection moulding and powder metallurgy. Detailed analysis of powders, binders, injection moulding, binder removal process and parameter optimization process is discussed. Taguchi method can also be applied for optimal design configurations when significant interactions exist between and among the controlled variables. This paper provides an overview of MIM process, optimization of parameters using Taguchi method.